Ascl1 phospho-site mutations enhance neuronal conversion of adult cortical astrocytes in vivo - Ghazale, Hussein; Park, EunJee; Vasan, Lakshmy; Mester, James; Saleh, Fermisk; Trevisiol, Andrea; Zinyk, Dawn; Chinchalongporn, Vorapin; Liu, Mingzhe; Fleming, Taylor; Prokopchuk, Oleksandr; Klenin, Natalia; et al. (Frontiers in Neuroscience, 2022)
Direct neuronal reprogramming, the process whereby a terminally differentiated cell is converted into an induced neuron without traversing a pluripotent state, has tremendous therapeutic potential for a host of neurodegenerative diseases. While there is strong evidence for astrocyte-to-neuron conversion in vitro, in vivo studies in the adult brain are less supportive or controversial. Here, we set out to enhance the efficacy of neuronal conversion of adult astrocytes in vivo by optimizing the neurogenic capacity of a driver transcription factor encoded by the proneural gene Ascl1. Specifically, we mutated six serine phospho-acceptor sites in Ascl1 to alanines (Ascl1SA6) to prevent phosphorylation by proline-directed serine/threonine kinases. Native Ascl1 or Ascl1SA6 were expressed in adult, murine cortical astrocytes under the control of a glial fibrillary acidic protein (GFAP) promoter using adeno-associated viruses (AAVs). When targeted to the cerebral cortex in vivo, mCherry+ cells transduced with AAV8-GFAP-Ascl1SA6-mCherry or AAV8-GFAP-Ascl1-mCherry expressed neuronal markers within 14 days post-transduction, with Ascl1SA6 promoting the formation of more mature dendritic arbors compared to Ascl1. However, mCherry expression disappeared by two-months post-transduction of the AAV8-GFAP-mCherry control-vector. To circumvent reporter issues, AAV-GFAP-iCre (control) and AAV-GFAP-Ascl1 (or Ascl1SA6)-iCre constructs were generated and injected into the cerebral cortex of Rosa reporter mice. In all comparisons of AAV capsids (AAV5 and AAV8), GFAP promoters (long and short), and reporter mice (Rosa-zsGreen and Rosa-tdtomato), Ascl1SA6 transduced cells more frequently expressed early- (Dcx) and late- (NeuN) neuronal markers. Furthermore, Ascl1SA6 repressed the expression of astrocytic markers Sox9 and GFAP more efficiently than Ascl1. Finally, we co-transduced an AAV expressing ChR2-(H134R)-YFP, an optogenetic actuator. After channelrhodopsin photostimulation, we found that Ascl1SA6 co-transduced astrocytes exhibited a significantly faster decay of evoked potentials to baseline, a neuronal feature, when compared to iCre control cells. Taken together, our findings support an enhanced neuronal conversion efficiency of Ascl1SA6 versus Ascl1, and position Ascl1SA6 as a critical transcription factor for future studies aimed at converting adult brain astrocytes to mature neurons to treat disease.